SISTEM MONITORING PENGUMPULAN GETAH KARET BERBASIS SMS GATEWAY PADA PETANI KARET DI DESA SURYA ADI KABUPATEN OKI PROVINSI SUMATERA SELATAN - Maya Amelia (UNIVERSITAS INDO GLOBAL MANDIRI)
Rubber is a prayer One commodity Commodity Indonesia And Many cultivated by 'community in South Sumatra. Based on the Field Study, hearts HAL rubber cultivation society The rubber gardens at generally involve role of workers tappers hearts management. Garden owners do a revenue share arrangement with eavesdroppers. However, taxable income accumulated rubber latex tappers then sell them AT broker Direct sap. Thus, the owner of the garden can be aware with no Definitely Period The collected sap findings. Only garden owners know the amount by Info From tapper thus possible fraud. By because why, On Development Research conducted monitoring system Singer collecting rubber latex-based SMS gateway to Solve the problem. The system is built using the PHP programming language With And MySQL database using With model as the waterfall model of system development. Searching Google Pages existence of the system, the owner of the garden will be watching the results can gum Yang collected from his garden Operates more Accurate than ever. Key words: SMS Gateway, monitoring systems, latex rubber.